2021
DOI: 10.3390/ma14112781
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Reclaimed Asphalt Pavement Modified with Waste Frying Oil and Crumb Rubber

Abstract: Researchers are exploring the utilisation of reclaimed asphalt pavement (RAP) as a recycled material to determine the performance of non-renewable natural aggregates and other road products such as asphalt binder, in the construction and rehabilitation stage of asphalt pavements. The addition of RAP in asphalt mixtures is a complex process and there is a need to understand the design of the asphalt mixture. Some of the problems associated with adding RAP to asphalt mixtures are moisture damage and cracking dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The CR, retained in a 0.15 mm sieve (mesh 40) by the Miroad Rubber Industry, Johor, Malaysia, was used. This study conducted the penetration, softening point, ductility, and viscosity tests to determine the WFO and CR contents [30].…”
Section: Methodsmentioning
confidence: 99%
“…The CR, retained in a 0.15 mm sieve (mesh 40) by the Miroad Rubber Industry, Johor, Malaysia, was used. This study conducted the penetration, softening point, ductility, and viscosity tests to determine the WFO and CR contents [30].…”
Section: Methodsmentioning
confidence: 99%
“…The crumb rubber and waste frying oil can restore the properties of RAP asphalt, especially its rheological properties, and also improve the compatibility and storage stability of RAP binder [ 17 ]. It was identified by Bilema et al [ 18 ] that waste frying oil could restore the mechanical properties such as the tensile strength ratio of recycled asphalt pavement, and crumb rubber could improve the rutting resistance of asphalt mixture, which are complementary to each other. Additionally, when pretreated with WCO at high temperatures, the three-dimensional network structure in crumb rubber is swollen and the interaction between rubber chains is weakened, which consequently leads to cross-linked bonds such as S-S and S-C with comparatively low bond energy being broken, and the soluble linear rubber molecular chains, carbon black fragments and other medium and small molecular weight substances are released [ 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was observed that appropriate RAP content has a significant effect on the performance of hot recycled asphalt mixture [23][24][25][26][27]. Bilema, M. et al [28] concluded that this enhanced stiffness and rutting resistance of the RAP but lowered moisture resistance, and the pavement sustainability and rutting performance of RAP could be restored by adding WFO and CR. Yin, P. et al [29] found that with the addition of RAP, high-temperature performance of HRAM increased and the low-temperature performance and moisture susceptibility decreased.…”
Section: Introductionmentioning
confidence: 99%